The psychosocial interactions of adolescent and young adult (AYA) cancer survivors and the possible relationship with their development : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Palmerston North, New Zealand - Cameron, Nicole (Massey University, 2019)
Adolescents and Young Adults (AYAs) with cancer may be particularly affected by social interactions, as they can be grappling with both a serious illness and normal developmental challenges. The present research aims to increase the understanding of the psychosocial interactions of AYAs with cancer and how these interactions can be grouped and organised in relation to each other. Furthermore, this research hopes to examine the relationship that cancer has with the developmental trajectory of this population, and how social interactions influence this relationship. As development is an important aspect of this age group, it is appropriate to consider both psychosocial interactions and the development of AYA survivors. Qualitative interviews asked ten participants (aged 16-25 years) to describe their psychosocial interactions and examined how these might affect their development. Thematic analysis identified a range of themes including: the importance of personal privacy and controlled sharing of information, independence, identity formation, positivity, acknowledgement of cancer vs. being treated normally, and receiving support instead of supporting others. In the one year follow-up interviews with five participants, half of these themes remained constant; however the personal privacy, independence and supporting others themes changed. Development appeared to be impacted by cancer for both adolescents and young adults, but this impact lessened over a one-year period. A quantitative study followed, which involved asking thirty AYAs to sort psychosocial interactions using a GOPA card-sort process, resulting in a multidimensional model of interactions. Interactions were derived from a combination of the aforementioned interviews, and a similar model completed for an Honours thesis. This model showed that AYAs conceptualise interactions in two main ways: through their perception of emotional response (avoidance/discomfort interactions opposed support interactions) and empathy (empathic actions/encouragement interactions opposed thoughtlessness interactions). Unfortunately the sample size was too small to complete two separate models comparing age differences, and therefore an understanding of developmental disparities in conceptualising interactions was unable to occur. Overall, social interactions and developmental stage appear to influence AYAs’ experience of cancer. Together, these two studies provide an understanding of how AYAs in New Zealand experience and perceive psychosocial interactions. Furthermore, there is an enhanced understanding of the developmental impact that cancer has on AYAs’ interactions. This research proudly contributes to the body of knowledge on AYAs in New Zealand, their psychosocial needs and the way cancer impacts on their development.
Keywords: Cancer in adolescence; Social aspects; Psychological aspects; Treatment; Complications; New Zealand; Cancer; Patients; Teenagers; Youth; Attitudes; 520302 Clinical psychology